Whiteness and Public Theology: an Exploration of Listening - Wyngaard, Cobus van ca. 21. Jh. (Missionalia, 2015)
This article explores how whiteness continues to remain a problem when working towards a public discourse which seeks the common good. Recognising that a public sphere where all can participate as equals is a space available only to a certain class of people, it asks what the implication of this recognition would be for those who do indeed live in a position where they can participate in forming public opinion and policy. Exploring the discussions resulting from Samantha Vices article titled How do I live in this strange place?, a listening which leads to a deeper recognition of my own complicity in injustice is described as an important part of public theology for white South Africans. The particular responsibility of working against the injustice from which I benefit is furthermore pointed out as a specific task which white public theologians need to take upon themselves.